2022
DOI: 10.1016/j.ssmph.2022.101035
|View full text |Cite
|
Sign up to set email alerts
|

Income trajectories and self-rated health status in the UK

Abstract: In line with the wide recognition of the connection between socioeconomic status and health outcomes, attention in the recent literature is extending the static perspective to the dynamic implications of income on health. This study contributes to the growing literature on the income-health nexus by evaluating income dynamics on various self-rated health measures in the UK. We explore the impact of different indicators of income experiences on self-rated health and wellbeing outcomes using data from the 11 Wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 58 publications
4
8
0
Order By: Relevance
“…The findings also support those of Akanni, Lenhart and Morton’s [ 47 ] longitudinal fixed-effects model for health and wellbeing outcomes using Understanding Society data in relation to all ages. They found that household real disposable income positively affects general health, mental health, and life satisfaction.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The findings also support those of Akanni, Lenhart and Morton’s [ 47 ] longitudinal fixed-effects model for health and wellbeing outcomes using Understanding Society data in relation to all ages. They found that household real disposable income positively affects general health, mental health, and life satisfaction.…”
Section: Discussionsupporting
confidence: 85%
“…Using several models to estimate cross-sectional regressions of health and wellbeing outcomes using longitudinal income information, they also found that long-term income and income position stability increases the likelihood of reporting improved physical and mental health and increased satisfaction with leisure and life. [ 47 p7]. This reflects Whitfield, Betancur, Miller and Votruba-Drzal’s [ 48 ] findings using data from young adults and their families in the National Longitudinal Study of Youth (NLSY79) and its Young Adult Survey supplement (NLSY-YA).…”
Section: Discussionsupporting
confidence: 52%
“…For respondents whose household per capita income was 5,594 yuan, when their income increases by 10%, the probability of reporting a good health condition increase by 0.004. This result is comparable to Akanni et al (2022) who explore income trajectories and self-rated health status in the UK and find that increased household income is associated with an increased likelihood of reporting excellent general health outcomes. Some studies also find that individuals who reported excellent health have higher household incomes than those likely to report a lower self-rated health category (Davillas et al, 2019).…”
Section: Regression Resultssupporting
confidence: 75%
“…It is recommended the significance of bone marrow sample for the initial immunophenotyping test in children, while subsequent analyses could be performed using peripheral blood [141]. Adults can undergo the initial stage of immunophenotyping using peripheral blood samples [142,143]. Reagents like Cyto-Chex and formaldehyde may be effective in prolonging the time that blood is stored while waiting for the conductance of cytometry.…”
Section: Immunologymentioning
confidence: 99%